The atypical antipsychotics olanzapine and quetiapine, but not haloperidol, reduce ACTH and cortisol secretion in healthy subjects - Cohrs, Stefan; Röher, Cornelia; Jordan, Wolfgang; Meier, Andreas; Huether, Gerald; Wuttke, Wolfgang; Rüther, Eckart; Rodenbeck, Andrea (Psychopharmacologia, 2006)
Increased activity of the hypothalamic-pituitary-adrenal (HPA) axis is an important aspect of the pathophysiology of major depression and schizophrenia. Despite the usefulness of atypical antipsychotics in the treatment of depression and their positive influence on cognitive functioning possibly related to their impact on cortisol, little is known about their effect on HPA axis function. Therefore, this double-blind, placebo-controlled, randomized cross-over study investigated the influence of the atypical antipsychotics quetiapine and olanzapine in comparison with haloperidol and placebo on plasma adrenocorticotropic hormone (ACTH), cortisol, and prolactin levels. Eleven healthy male volunteers were studied during four sessions one week apart, orally receiving placebo, quetiapine (50 mg), olanzapine (5 mg), or haloperidol (3 mg). Blood samples were taken at hourly intervals from 0900 until 1700 hours. For ACTH, cortisol, and prolactin a significant effect of treatment condition (p < or = 0.005; p < or = 0.035; p < or = 0.0001, respectively) for area under the curve (AUC) was found. In comparison to placebo, quetiapine and olanzapine significantly reduced ACTH (p < or = 0.002; p < or = 0.05, respectively) and cortisol (p < or = 0.005; p < or = 0.03, respectively). No effect of haloperidol on AUC of ACTH or cortisol levels was observed. In comparison with placebo, haloperidol (p < or = 0.0001) and olanzapine (p < or = 0.0001) elevated AUC of prolactin plasma levels, whereas no significant effect was observed for quetiapine as a main effect of treatment condition. The atypical antipsychotics' strong influence on HPA-function with pronounced ACTH and cortisol lowering is possibly related to the atypicals' blockade of serotonergic receptors, but blockade of adrenergic or histaminergic receptors may play a role as well. The observed HPA-axis down-regulation may be clinically important for the atypicals' effects on depressive symptomatology and cognitive functioning.